Designing Reborn Mental Health Applications Using Lean UX Methods - Rizal Ramdhani, Muhammad; Muhammad Yan Handita (Information Technology International Journal, 2025)
Faster technology is essential today in terms of providing and presenting information sources. The rise of social media and all its sources and platforms is one of the drivers for this research. Mental health issues further form the background of this research. The Reborn app promotes the use of technology and is designed for people with mental health issues who need quick advice and professional treatment. The Lean UX model is a good method because it helps to achieve success and success faster when designing apps. The results obtained in this research constitute the final prototype and will be verified in terms of criticism and suggestions through a questionnaire as part of the evaluation of the Reborn app. Positive UX and good usability are essential for the further development of the application prototype. the results of the UI usability value are excellent with an SUS score of 82, which is above average and accepted by users